PENINGKATAN KOMPETENSI DASAR MATA PELAJARAN AGAMA ISLAM SEKOLAH DASAR HANG TUAH V JAKARTA MELALUI STRATEGI PEMBELAJARAN ACTIVE LEARNING - Syarifah Hanum (Perspektif Ilmu Pendidikan, 2009)
The purpose of this research was to know the improvement of basic competency of Islamic Religion Subject through active learning strategy. This research was held in the second year of Hang Tuah V Elementary School Jakarta, in the second semester, 2007/ 2008 academic year. The design of this research involved 4 steps: (1) planning, (2) acting, (3) observing, and (4) reflecting. The result of this research was that there was an increase between the means of first cycle and of the second one, 67 and 81 respectively. Furthermore, most of active learning aspects observed progressed between the first cycle and the second one, 64 % and 80 % respectively. It can be concluded that application of active learning strategy in Islamic Religion Subject can improve the competencies of students in the second year of Hang Tuah V elementary school in Jakarta.